High-temperature-resistant and strong-alkali-resistant composite defoaming agent for PCB film stripping and developing and preparation method thereof
Patent Information
- Application Number
- CN202611391791.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-13
AI Technical Summary
大量泡沫会造成多重生产问题:泡沫溢出槽体,造成药液浪费与现场安全隐患;泡沫隔绝药水与板面接触,引发退膜、显影不均,线路良率下降;泡沫携带树脂污染物流入水洗工序,持续降低板面清洗效果
本发明通过“复合硅膏快速破泡+聚醚改性有机硅持久抑泡+疏水气相SiO2桥联脱稳”的三元协同机制,在PCB退膜液中添加0.1%时,Ross-Miles法破泡时间≤8秒,抑泡持续时间≥30分钟,解决了现有消泡剂普遍存在的“破泡快但抑泡短”或“抑泡长但破泡慢”的矛盾,实现了快慢双速协同的长效消泡。
Smart Images

Figure CN122894764A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional additives for wet processing of printed circuit boards, specifically to a high-temperature resistant, strong alkali-resistant composite defoamer for PCB stripping and development, and its preparation method. Background Technology
[0002] In printed circuit board (PCB) manufacturing, stripping and developing are core wet processes for pattern transfer. Both processes generate a large amount of foam due to high-pressure spraying, necessitating the addition of defoamers to ensure stable production. The stripping process uses a high-concentration NaOH or alkali-amine mixture at 55-80℃ to peel off the dry photoresist film, while the developing process uses a sodium carbonate solution at 28-32℃ to rinse the photosensitive resin. Excessive foam causes multiple production problems: foam overflows from the tank, wasting chemicals and creating safety hazards; foam prevents the chemicals from contacting the board surface, leading to uneven stripping and developing, and reduced circuit yield; foam carries resin contaminants into the washing process, continuously reducing the cleaning effect on the board surface.
[0003] From the perspective of the entire wastewater treatment lifecycle, membrane stripping and developing wastewater are high-alkalinity, high-COD, and high-organic-pollutant recalcitrant wastewater. The residual defoamer in the wastewater directly determines the effectiveness of biological treatment. If the defoamer is difficult to biodegrade, it will continuously inhibit the activity of activated sludge microorganisms, impair sludge settling performance, and significantly increase the wastewater treatment load and operation and maintenance costs in the long run. Therefore, high-quality defoamers must not only meet the requirements of production conditions but also possess excellent biodegradability to reduce the pressure on downstream pollution control. Existing products find it difficult to simultaneously meet both of these requirements.
[0004] Currently, mainstream defoamers on the market all have obvious defects: traditional emulsified silicone oil has a decent instantaneous defoaming effect, but it is very easy to break emulsion and float oil under high temperature and strong alkaline environment. The silicone oil precipitates and adheres to the board surface to form stubborn silicone spots, which interfere with subsequent electroplating and solder resist bonding. Silicone residues cannot be biochemically degraded, and long-term accumulation damages the wastewater biological treatment system; pure polyether defoamers have good water solubility. Chinese patent CN117398724A is a typical example. It relies on propylene glycol and ethylene oxide to synthesize polyether as the main body and compounded with anti-corrosion additives. However, in a strong alkaline environment above 60°C, the polyether segments of this system are prone to alkaline catalytic oxidation degradation, and the defoaming activity decays rapidly. The lactone additives in the formula will also undergo saponification and hydrolysis. The hydrolysis products will generate new foam and further increase the COD of the waste liquid.
[0005] General-purpose silicone polyether products such as BYK and Tego series simply mechanically mix silicone oil and polyether. When faced with a combination of conditions including pH>12, high temperature, and high spray shear, the emulsion balance is easily disrupted, resulting in silicone oil precipitation and silicone spots. At the same time, they generally have a problem with inconsistent defoaming and foam suppression performance. Either the defoaming is slow or the foam suppression is short, and the effective usage time under continuous spray conditions is less than 4 hours, requiring frequent replenishment, which further increases the amount of additive residues in the waste liquid.
[0006] Chinese patent CN105561634A prepares cross-linked silicon network compound silicone paste through hydrosilylation, which improves temperature and alkali resistance to a certain extent. However, the system only has two active components and does not have a dedicated long-lasting antifoaming polyether modified organosilicon. The cross-linked silicon network is too rigid and is difficult to spread in the foam liquid film. Under high shear, the antifoaming performance declines rapidly, and the antifoaming time has a significant shortcoming.
[0007] In summary, existing PCB stripping and developing defoamers are ill-suited to the harsh conditions of high temperature, strong alkali, and continuous high-shear spraying. They generally suffer from process defects such as emulsion stratification and oil leaching, silicone residue on the board surface, imbalanced defoaming and foam suppression performance, and high agent consumption. Furthermore, their formulation designs neglect wastewater treatment requirements, and residual additives inhibit the operation of biological systems. The industry urgently needs to develop a ternary synergistic composite defoamer that achieves rapid foam breaking, long-lasting foam suppression, stability without stratification under strong alkali and high temperature conditions, and no silicone residue on the board surface. It also possesses good biodegradability, meeting the dual needs of production processing and end-of-pipe wastewater treatment. Summary of the Invention
[0008] Therefore, this invention provides a high-temperature resistant, strong alkali-resistant composite defoamer for PCB delamination and development, and its preparation method, to solve the problems in the prior art.
[0009] To achieve the above objectives, the present invention provides the following technical solution: According to a first aspect of the present invention, a high-temperature resistant, strong alkali-resistant composite defoamer for PCB stripping and developing comprises, by weight percentage: 5-18% organosilicon defoaming active ingredient, 15-35% polyether-modified organosilicon dispersion, 1-5% hydrophobic fumed silica, 3-10% nonionic emulsifier, 0.5-3% thickening stabilizer, and the balance being deionized water. The organosilicon defoaming active ingredient is a composite silicone paste of hydroxyl-terminated polydimethylsiloxane and silicone resin, which is prepared by a condensation reaction between hydroxyl-terminated polydimethylsiloxane and silicone resin. The composite defoamer does not exhibit oil bleed or stratification in strongly alkaline media with a pH of 11-14, and its operating temperature range is 25-85℃.
[0010] Furthermore, the silicone resin is selected from one or more of MQ silicone resin, MT silicone resin, and T silicone resin; the mass ratio of the terminal hydroxyl polydimethylsiloxane to the silicone resin is (2-10):1; the condensation reaction temperature is 100-180℃, and the time is 1-6 hours. The silicone resin is MQ silicone resin, and the M:Q ratio is 0.5-1.0.
[0011] Furthermore, the polyether-modified organosilicon dispersion is prepared by hydrosilylation reaction of allyl polyoxyethylene polyoxypropylene ether and hydrogen-containing silicone oil, or by condensation reaction of hydroxyl-terminated polyether and hydrogen-containing silicone oil, or by free radical graft copolymerization of polyether and dimethyl silicone oil; the EO / PO molar ratio of its polyether side chain is (1-6):1, the number average molecular weight Mn is 800-5000, and the cloud point is 45-90℃.
[0012] As an example, the condensation reaction is a dehydration condensation reaction between the Si-OH of the hydroxyl-terminated polydimethylsiloxane and the Si-OH of the silicone resin, with a reaction temperature of 100-180℃ and a reaction time of 1-6 hours, without the need for an external catalyst.
[0013] The viscosity of the hydroxyl-terminated polydimethylsiloxane at 25°C is 50-2000 cSt.
[0014] Furthermore, the specific surface area of the hydrophobic fumed silica is 150-300 m². 2 / g, with a contact angle ≥130° after hydrophobic surface treatment with hexamethyldisilazane or dimethyldichlorosilane.
[0015] Furthermore, the nonionic emulsifier is selected from two or more of the following compound systems: sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, alkylphenol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether, and the weighted average HLB value after compounding is 8-13.
[0016] As an example, the nonionic emulsifier is a blend of Span 60 and Tween 60, with a mass ratio of Span 60 to Tween 60 of (1-3):1 and an HLB value of 9-12.
[0017] Furthermore, the thickening stabilizer is selected from one or more of xanthan gum, sodium carboxymethyl cellulose, sodium polyacrylate, hydroxyethyl cellulose, and guar gum.
[0018] A method for preparing a composite defoamer as described above, according to a second aspect of the present invention, includes the following steps: a) Mix hydroxyl-terminated polydimethylsiloxane with silicone resin in a certain proportion, stir and react at 100-180℃ for 1-6 hours, and obtain composite silicone paste after cooling. b) Dissolve the nonionic emulsifier in deionized water at 60-70℃, add the composite silicone paste, and emulsify at high speed of 3000-5000rpm for 15-30 minutes to obtain the silicone paste emulsion. c) Add the polyether-modified organosilicon dispersion to the remaining deionized water and stir to disperse evenly; d) Combine the emulsions obtained in steps b and c, add hydrophobic fumed silica, and continue high-speed shearing for 10-20 minutes; e) Add a thickening stabilizer to adjust the viscosity to 500-2000 mPa·s (25℃) to obtain the composite defoamer.
[0019] Furthermore, the reaction temperature in step a is 120-160℃, and the reaction time is 2-4 hours.
[0020] The application of the composite defoamer as described above, provided by the third aspect of the present invention, in the PCB stripping process or the PCB developing process.
[0021] Furthermore, when applied to the film stripping process, the film stripping solution is an alkaline NaOH system or a mixed alkaline NaOH / organic amine system, with an operating temperature of 55-80℃ and an antifoaming agent addition amount of 0.05-0.3wt%; when applied to the developing process, the developing solution is a Na2CO3 system, with an operating temperature of 28-32℃ and an antifoaming agent addition amount of 0.02-0.1wt%.
[0022] The present invention has the following advantages: This invention utilizes a ternary synergistic mechanism of "rapid defoaming of composite silicone paste + long-lasting defoaming of polyether-modified organosilicon + bridging and destabilization of hydrophobic vapor-phase SiO2". When added to PCB stripping solution at 0.1%, the Ross-Miles defoaming time is ≤8 seconds and the defoaming duration is ≥30 minutes. This solves the contradiction of existing defoamers being "fast defoaming but short defoaming" or "long defoaming but slow defoaming", and achieves long-lasting defoaming with a synergistic effect of fast and slow defoaming.
[0023] This invention utilizes a hydroxyl-terminated polydimethylsiloxane and MQ silicone resin to prepare a composite silicone paste via a Si-OH condensation reaction. The high bond energy of the Si-O-Si bonds endows the silicone paste with extremely high thermal stability and chemical inertness. Combined with a saponification-resistant saturated fatty acid ester emulsifier and a xanthan gum thickening and protective system, the defoamer does not separate or exhibit oil floating after 96 hours of storage under strongly alkaline conditions at pH 11-14 and 80℃. The FTIR characteristic peak area change is <3%, and the service life is significantly longer than existing products.
[0024] This invention controls the particle size D of silicone paste microdroplets. 50 <3μm, combined with nonionic emulsifier to form a dense adsorption layer at the oil-water interface, the defoamer is evenly dispersed in the stripping solution, after the titanium plate is soaked for 24 hours the water contact angle is <50°, and there is no silicone spot residue on the plate surface, avoiding the technical defects of traditional organosilicon defoamers that affect the subsequent electroplating and solder resist bonding due to oil adhering to the plate surface.
[0025] The components of this invention do not contain persistent harmful ingredients that are difficult to degrade or inhibit microorganisms under strong alkaline conditions. The emulsifier is selected from saturated fatty acid esters, and the thickener is selected from biodegradable natural polymer materials such as xanthan gum. After the defoamer enters the wastewater treatment system with the membrane stripping waste liquid, it will not significantly inhibit the activated sludge microorganisms, which is conducive to ensuring the stable operation of the subsequent biochemical treatment system and the compliance of the effluent.
[0026] This invention employs an emulsification system that matches the HLB value with a nonionic emulsifier, combined with a weak gel network formed by xanthan gum in the continuous phase, which effectively resists the buoyancy aggregation of silicone oil droplets and Ostwald curing, giving the defoamer storage stability of ≥6 months under normal and high temperature conditions, facilitating industrial production and storage and transportation.
[0027] The preparation of the composite silicone paste of this invention does not require the addition of an external catalyst and can be completed solely through a thermally driven condensation reaction, thus avoiding the use and residue problems of platinum catalysts, reducing production costs and process complexity; the subsequent emulsification process can be achieved using conventional high-speed shearing equipment, with mild operating conditions, making it easy to scale up for industrial production. Attached Figure Description
[0028] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.
[0029] The structures, proportions, sizes, etc. illustrated in this specification are only for the purpose of assisting those skilled in the art in understanding and reading the content disclosed herein, and are not intended to limit the conditions under which the present invention can be implemented. Therefore, they have no substantial technical significance. Any modifications to the structure, changes in the proportions, or adjustments to the size, without affecting the effects and objectives that the present invention can produce, should still fall within the scope of the technical content disclosed in the present invention.
[0030] Figure 1 Particle size distribution of the finished composite defoamer from Examples 1-3 provided for the test examples of this invention; Figure 2 The FTIR infrared spectra of the composite defoamer of Example 1 provided as a test example of the present invention before and after aging at 80℃ / pH13 for 72 hours are compared; where A is before aging; B is after aging. Detailed Implementation
[0031] The following specific embodiments illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Unless otherwise specified in the embodiments of this invention, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all commercially available products; different manufacturers and models of raw materials do not affect the implementation of the technical solution or the achievement of the technical effect of this invention.
[0033] The raw materials are shown in Table 1.
[0034] Table 1 Raw Material List
[0035] Example 1 Prepare the composite defoamer (total feed amount 100g) according to the following steps: a) Preparation of silicone paste: 8.3g of hydroxyl-terminated PDMS (viscosity 350cSt, 25℃) and 1.7g of MQ silicone resin (M:Q ratio = 0.75) were added to a reaction vessel, heated to 150℃ under N2 protection, stirred at 200r / min for 3 hours, and cooled to 25℃ to obtain composite silicone paste (PDMS:MQ = 5:1, appearance is transparent viscous liquid, viscosity is about 8500mPa·s).
[0036] b) Emulsification: Dissolve 3g of Span 60 and 3g of Tween 60 in 30g of deionized water (preheated to 65℃), add 10g of the composite silicone paste obtained in step a, and emulsify for 20 minutes at 4000rpm using a high-speed shear emulsifier (jacket insulation at 55-60℃) to obtain a milky white O / W type silicone paste emulsion.
[0037] c) Dispersion: Add 25g of polyether-modified organosilicon dispersion (EO / PO=3:1, Mn≈2000, cloud point 62℃) to 25g of deionized water, stir at 300r / min for 10 minutes to disperse evenly, and obtain polyether dispersion.
[0038] d) Combining: Pour the polyether dispersion obtained in step c into the emulsion obtained in step b, add 3g of hydrophobic vapor phase SiO2 (Aerosil R974), and continue to shear at 4000rpm for 15 minutes.
[0039] e) Thickening: Add 1g of xanthan gum, stir at 300r / min for 20 minutes until completely dissolved, and degas under vacuum (-0.08MPa, 5 minutes) to obtain the finished composite defoamer.
[0040] Example 2 Prepare the composite defoamer (total feed amount 100g) according to the following steps: a) Preparation of silicone paste: 5.3g of hydroxyl-terminated PDMS (viscosity 65cSt, 25℃) and 0.7g of MQ silicone resin (M:Q ratio = 0.9) were added to the reactor. The temperature was raised to 140℃ under N2 protection and stirred at 200r / min for 4 hours. After cooling, composite silicone paste (PDMS:MQ = 8:1) was obtained.
[0041] b) Emulsification: Dissolve 2g of Span 60 and 2g of Tween 60 in 25g of deionized water (preheated to 65°C), add 6g of the composite silicone paste obtained in step a, and emulsify for 15 minutes at 3500rpm using a high-speed shear emulsifier to obtain an O / W type silicone paste emulsion.
[0042] c) Dispersion: Add 30g of polyether-modified organosilicon dispersion (EO / PO=5:1, Mn≈3000, cloud point 78℃) to 33g of deionized water, stir at 300r / min for 10 minutes to disperse evenly, and obtain polyether dispersion.
[0043] d) Combining: Pour the polyether dispersion obtained in step c into the emulsion obtained in step b, add 1.5g of hydrophobic vapor phase SiO2 (Aerosil R812S), and continue to shear at 3500rpm for 10 minutes.
[0044] e) Thickening: Dissolve 0.5g of CMC-Na in a small amount of deionized water and add it to the emulsion. Stir at 300r / min for 15 minutes until uniform. Defoam under vacuum to obtain the finished composite defoamer.
[0045] Example 3 Prepare the composite defoamer (total feed amount 100g) according to the following steps: a) Preparation of silicone paste: 11.25g of hydroxyl-terminated PDMS (viscosity 750cSt, 25℃) and 3.75g of MQ silicone resin (M:Q ratio = 0.6) were added to the reaction vessel, heated to 160℃ under N2 protection, and stirred at 200r / min for 2 hours. After cooling, composite silicone paste (PDMS:MQ = 3:1) was obtained.
[0046] b) Emulsification: Dissolve 4g of Span 60 and 3g of Tween 60 in 28g of deionized water (preheated to 70℃), add 15g of the composite silicone paste obtained in step a, and emulsify for 25 minutes at 5000rpm using a high-speed shear emulsifier (jacket insulation at 55-60℃) to obtain an O / W type silicone paste emulsion.
[0047] c) Dispersion: Add 20g of polyether-modified organosilicon dispersion (EO / PO=2:1, Mn≈1500, cloud point 55℃) to 24g of deionized water, stir at 300r / min for 10 minutes to disperse evenly, and obtain polyether dispersion.
[0048] d) Combining: Pour the polyether dispersion obtained in step c into the emulsion obtained in step b, add 4g of hydrophobic vapor phase SiO2 (Aerosil R974), and continue to shear at 5000rpm for 18 minutes.
[0049] e) Thickening: Add 2g of sodium polyacrylate, stir at 400r / min for 20 minutes until completely dissolved, and degas under vacuum to obtain the finished composite defoamer.
[0050] Comparative Example 1 The only difference from Example 1 is that 10g of pure hydroxyl-terminated PDMS (viscosity 350cSt) is used instead of the composite silicone paste, i.e. MQ silicone resin is not added. The remaining components and preparation steps are exactly the same as in Example 1.
[0051] Comparative Example 2 The only difference from Example 1 is that hydrophobic vapor phase SiO2 (Aerosil R974) is not added; the other components and preparation steps are exactly the same as in Example 1.
[0052] Comparative Example 3 The only difference from Example 1 is that the polyether-modified organosilicon dispersion is not added, and the remaining components and preparation steps are exactly the same as in Example 1.
[0053] Comparative Example 4 Prepare defoamer by proportionally reducing the amount of raw materials (total amount approximately 100g): a) Synthesis of the network structure polymer: 8.6g of vinyl MQ silicone resin (vinyl content 4%, M:Q=0.8) and 11.4g of hydrogen-containing silicone oil (hydrogen content 0.1%, viscosity 200cSt) were added to a reactor. Under N2 protection, the temperature was raised to 100℃, and 0.02g of chloroplatinic acid catalyst (chloroplatinic acid isopropanol solution, Pt content about 8ppm) was slowly added dropwise. The temperature was raised to 120℃ and kept at that temperature for 3 hours to obtain about 20g of viscous network structure polymer.
[0054] b) Preparation of silicone paste: 8.9 g of the network polymer obtained in step a, and fumed silica (specific surface area 270 m²) were added. 21.0g of dimethyl silicone oil (viscosity 60000cSt), 6.0g of dimethyl silicone oil (viscosity 500cSt), and 4.0g of NaOH were mixed and added to the reaction vessel. The mixture was kept at 140℃ for 5 hours and then cooled to room temperature to obtain approximately 20g of silicone paste.
[0055] c) Emulsion preparation: Add 16g of the silicone paste obtained in step b, 6g of the ternary copolymer (allyl polyoxyethylene polyoxypropylene ethoxy ether and polyether polyol co-modified silicone oil), 2g of composite emulsifier A (Tween 80 and octadecyl polyoxyethylene ether compound), and 1g of composite emulsifier B (Arlacel 80 and diethylene glycol monostearate compound) to the emulsification kettle, stir and heat to 65°C, slowly add 45g of thickening water (aqueous solution containing thickener) within 30min, start homogenization for 5min, and then add the remaining 30g of thickening water to make the emulsion, which is the defoamer product.
[0056] Test case Performance tests were conducted on the embodiments and comparative examples: 1. Ross-Miles defoaming performance test The test was conducted in accordance with GB / T 7462 "Determination of foaming power of surfactants - Modified Ross-Miles method".
[0057] Film stripping test conditions: Prepare a 5% NaOH aqueous solution as a simulated film stripping solution and heat it to a constant temperature of 60℃. Add defoamer to a concentration of 0.1wt% (based on the total mass of the film stripping solution). Pour 200mL of foaming solution from a height of 450mm through a standard aperture into a bottom 200mL of the same liquid. Start timing immediately after pouring and record the initial foam height (H0) and the time required for the foam to break down to 50% of the initial height (bubble breaking time, t). 50 ), and the residual foam height after 30 minutes (H) 30 ).
[0058] Developing condition test conditions: Prepare a 1% Na2CO3 aqueous solution as a simulated developing solution and heat it to a constant temperature of 30℃. Add defoamer to a concentration of 0.05wt%, and perform the remaining operations as in the film stripping condition test.
[0059] 2. 10-cycle defoaming decay test In the same stripping solution (NaOH 5%, 60℃, containing 0.1wt% defoamer), 10 consecutive Ross-Miles defoaming cycles were performed. Each cycle was performed according to Test Method 1, and the defoaming time (t) of each cycle was recorded. 50 Once the foam has completely subsided, immediately proceed with the next pouring and foaming. Calculate the cycle decay rate: Decay rate (%) = (t) 50,10 -t 50,1 ) / t50,1 ×100%.
[0060] 3. High-temperature strong alkali stability test Add the defoamer to a 5% NaOH solution (pH≈13) to a concentration of 0.1wt%. Mix well, then transfer 200mL of the solution to a 500mL capped PP heat-resistant bottle. Seal the bottle and place it in an 80℃ drying oven for 96 hours. Observe and record the following daily: whether stratification occurs, whether oil floats, and color changes. After 96 hours, take a sample and measure its infrared spectrum using an FTIR infrared spectrometer (coating method or ATR method), paying particular attention to the Si-O-Si characteristic peak (1020-1090cm). -1 ) and Si-CH3 characteristic peak (1260 cm⁻¹) -1 The integral change rate (%) of the characteristic peak area was calculated by comparing the FTIR spectrum of the sample with that of the unaged sample.
[0061] 4. Defoaming performance retention rate test after high-temperature aging at 85℃ / 72h Add the defoamer to an 8% NaOH solution (pH≈13.5) to a concentration of 0.2wt%, mix well, and place in an 85℃ drying oven for 72 hours. After aging, test the defoaming time of the aged sample using the Ross-Miles method (NaOH 8%, 80℃) and compare it with the unaged sample to calculate the defoaming performance retention rate: Retention rate (%) = (defoaming time before aging / defoaming time after aging) × 100%.
[0062] 5. Silicone Paste Storage Modulus Test Take the silicone paste samples prepared in each example and comparative example, and perform frequency scanning (frequency 1Hz, strain 1%, 25℃) in oscillation mode using a rotational rheometer (flat plate fixture, diameter 25mm, gap 1mm), and record the storage modulus G' (Pa).
[0063] 6. Silicon spot test on board surface (contact angle method) Take a titanium plate sample (50×50mm), wipe it sequentially with anhydrous ethanol, rinse with deionized water, and dry it at 60℃ for 30 minutes. Measure the initial water contact angle (3 points are measured per plate, and the average value is taken). Immerse the titanium plate in a 5% NaOH stripping solution containing 0.1wt% defoamer at 60℃ for 24 hours. After removal, rinse with deionized water and dry at 60℃. Measure the water contact angle after treatment. A contact angle <50° is considered as no silicone spot residue, and a contact angle >80° is considered as having severe silicone spot contamination.
[0064] 7. Development resolution test After the FR-4 substrate coated with dry film photoresist is exposed and developed, defoamer is added to the Na2CO3 1% developer (30℃) to a concentration of 0.05wt%. After development, the circuit pattern is observed with a metallographic microscope to determine whether the line width / line spacing meets the design requirements (25 / 25μm) and whether there are uneven development or circuit defects caused by defoamer residue.
[0065] 8. Emulsion Particle Size Determination Take an appropriate amount of the defoamer emulsion prepared in each example, dilute it with deionized water to approximately 1:1000 (volume ratio), and measure the particle size distribution using a DLS dynamic light scattering instrument (Zetasizer Nano ZS90). Record the D... 50 (Median particle size) and D 90 (Percentile particle size).
[0066] 9. Emulsion viscosity determination Take an appropriate amount of the defoamer emulsion prepared in each example, and measure its viscosity using a rotational viscometer (NDJ-8S, rotor No. 2, speed 30 rpm) at a constant temperature of 25°C. Record the reading after it stabilizes.
[0067] 10. Continuous spray simulation test Prepare 10L of 5% NaOH stripping solution, add defoamer to a concentration of 0.1wt%, and heat to 60℃. Use a circulating pump (flow rate 3.5L / min) to pump the stripping solution from the bottom of the storage tank to a height of 300mm above the liquid surface for spray recirculation, simulating the high-shear spraying conditions of the production line. Run continuously for 30 minutes, recording the height of the foam layer (mm) every 5 minutes. A foam layer height <30mm is considered a safe operating threshold.
[0068] 11. Fourier Transform Infrared Spectroscopy (FTIR) Analysis The infrared spectra of the samples were determined using the coating method or the ATR method, with a scanning range of 4000-400 cm⁻¹. -1 4cm resolution -1 The number of scans was 32. Comparative Example 2 sample was monitored at a depth of 1735 cm. -1 The enhancement of the C=O characteristic peak was used to determine the degree of oxidative degradation of the polyether segments. The results are shown in Table 2.
[0069] Table 2 Performance test results of each embodiment and comparative example
[0070] As can be seen from Table 2, the emulsions D in Examples 1-3 50 The micrometers are 2.08 μm, 2.73 μm, and 1.52 μm, respectively, all less than 3 μm. For example... Figure 1The particle size distribution diagrams show that the particle size distributions of the three embodiments are all unimodal, with a narrow distribution width (D). 90 The particle sizes were 3.46 μm, 4.15 μm, and 2.79 μm, respectively, indicating that the emulsion system had a good emulsification effect on the three composite silicone pastes with different viscosities, and the emulsion particle size was controllable.
[0071] Example 1 showed a defoaming time of only 5.3 seconds in 5% NaOH stripping solution, a residual foam height of only 11 mm after 30 minutes, and a decay rate of only 15% after 10 cycles. Example 3 showed a defoaming time of only 4.9 seconds under high temperature conditions of 80℃, and a defoaming performance retention rate of >95% after aging at 85℃ for 72 hours. All three examples simultaneously achieved rapid defoaming and long-term foam suppression, verifying the effectiveness of the ternary synergistic mechanism of "rapid defoaming of composite silicone paste + long-term foam suppression of polyether-modified organosilicon + hydrophobic vapor-phase SiO2 bridging and destabilization". Example 2 showed a defoaming time of 6.8 seconds under low alkalinity and low temperature conditions in the developer, a foam height of <10 mm after 40 minutes, and no abnormalities in the development resolution test, proving the adaptability of the present invention under development conditions and its non-interference with circuit accuracy.
[0072] In Comparative Example 1, replacing composite silicone paste with pure PDMS prolonged the initial defoaming time from 5.3 seconds to 17.8 seconds, with a decay rate as high as 89% after 10 cycles, and delamination occurred after aging at 80℃ for 96 hours. The core reason is that the storage modulus G' of pure PDMS silicone paste is only about 8 Pa, making it extremely prone to deformation and displacement to the Plateau boundary under the shear stress of the foam liquid film, leading to failure. In contrast, the three-dimensional Si-O-Si network of MQ silicone resin increases G' to about 580 Pa, allowing silicone paste droplets to remain stably within the liquid film and continuously exert their defoaming effect. At the same time, the chemical bonding structure formed by the condensation reaction between the Si-OH on the surface of MQ silicone resin and the Si-OH at the PDMS end gives the silicone paste higher cohesive strength, resisting phase separation under high temperature and strong alkaline conditions.
[0073] In Comparative Example 2, without the addition of hydrophobic vapor-phase SiO2, the bubble-breaking time increased from 5.3 seconds to 13.6 seconds, the foam height increased from 11 mm to 53 mm after 30 minutes, and the height of the continuously sprayed foam layer reached 55 mm after 30 minutes. The contribution of hydrophobic SiO2 is reflected in two aspects: in the defoaming stage, SiO2 aggregates form hydrophobic "protrusions" in the bubble liquid film, reducing the local radius of curvature of the liquid film and accelerating the mechanical instability of the liquid film; in the foam suppression stage, SiO2 / silicone paste composite microdroplets form an irreversible adsorption layer on the surface of the newly formed foam, inhibiting the Gibbs-Marangoni elastic self-healing of the foam liquid film. Without SiO2, relying solely on silicone paste spreading for bubble breaking lacks particle-liquid film synergy, resulting in a significant decrease in efficiency.
[0074] Comparative Example 3, without PMS, showed a foam breaking time of 12.8 seconds, a foam height of 68 mm after 30 minutes, and a 55% decay rate after 10 cycles. PMS is the sole contributor to the slow foam suppression dimension in the "fast-slow dual-speed synergy" of this invention: its comb-like molecular structure allows it to continuously diffuse to the surface of newly formed bubbles in the form of monomolecules / micelles and reduce the elasticity of the liquid film when the temperature is below the cloud point; when the temperature approaches the cloud point, it switches to particulate bridging and destabilization. The system without PMS relies solely on the rapid foam breaking effect of silicone paste and lacks the ability to suppress continuously generated new foam, thus its foam suppression performance deteriorates sharply. The presence of PMS enables a seamless transition in the foam suppression mode from "molecular occupancy" to "particulate bridging" in a temperature-responsive manner.
[0075] The hydrosilylation crosslinking route of Comparative Example 4 had an initial defoaming time of 9.5 seconds and a defoaming time of only 12 minutes. After 10 cycles, the defoaming time increased from 9.5 seconds to 38 seconds. The contact angle of the titanium plate after immersion was 78°, and micro-delamination appeared after aging at 80℃ for 96 hours.
[0076] Comparative Example 2 showed a defoaming time of 8 seconds in a neutral aqueous solution at 25°C. However, under alkaline conditions at 60°C, the polyether segments underwent alkaline-catalyzed oxidative degradation, causing the polyether cloud point to drop from 55°C to 32°C. The defoaming active molecules precipitated too quickly from the aqueous phase, resulting in loss of dispersibility. This formulation exhibited yellowing and stratification after 53 days at pH 13 / 60°C, further verifying the insufficient long-term stability of the pure polyether system under high-temperature, strongly alkaline conditions due to chemical degradation.
[0077] Examples 1-3 showed no stratification or oil drift after standing for 96 hours at 80℃ / pH13, and the FTIR characteristic peak area change was <2%, demonstrating the high-temperature strong alkali chemical inertness of the Si-O-Si backbone and the stability of the emulsion system. Figure 2 The FTIR spectrum comparison diagram of Example 1 shows that the characteristic peaks of Si-O-Si before and after aging (1020-1090 cm⁻¹) are different. -1 ) and Si-CH3 characteristic peak (1260 cm⁻¹) -1 The peak shape and position were basically consistent, and no new characteristic peaks were observed, further confirming the chemical stability of the composite silicone paste under high temperature and strong alkaline conditions. Combined with a saponification-resistant saturated fatty acid ester emulsifier and xanthan gum thickening and protection, long-term stability of the emulsion under extreme conditions was achieved. Comparative Example 1 showed stratification, and Comparative Example 4 showed micro-stratification, further verifying the advantages of this invention in high temperature and strong alkaline stability.
[0078] Example 1: After immersion, the water contact angle of the titanium plate was 42.4°, demonstrating no residual silicon spots. This invention controls the emulsion particle size D... 50<3μm emulsifiers form a dense adsorption layer at the oil-water interface, effectively preventing silicone oil droplets from adhering to the board surface. Comparative Example 4, with a titanium plate contact angle of 78°, exhibits slight silicone spots. This is because the hydrosilylation crosslinking product itself has high surface energy, its emulsion particle size distribution is wide, and the emulsifier system was not optimized for PCB board surface residue.
[0079] Example 1 exhibits the best overall performance under film removal conditions and is the preferred formulation specifically for film removal. Example 2 has a lower silicone paste viscosity and slightly larger emulsion particle size, but it suppresses foaming for over 40 minutes under low-alkalinity and low-temperature developer conditions without affecting development resolution, making it the preferred formulation specifically for developer applications. Example 3 has the highest silicone paste viscosity, the smallest emulsion particle size, and the fastest foam breaking, with a retention rate >95% after aging at 85℃ / 72h, making it suitable for high-temperature film removal conditions at 80℃. These three examples, by adjusting PDMS viscosity, PDMS:MQ ratio, and emulsification parameters, optimized performance under different application scenarios, demonstrating the adjustability and wide adaptability of the formulations in this invention.
[0080] Although the present invention has been described in detail above with general descriptions and specific embodiments, modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, all such modifications or improvements made without departing from the spirit of the present invention fall within the scope of protection claimed by the present invention.
Claims
1. A high-temperature resistant, strong alkali-based composite defoamer for PCB stripping and developing, characterized in that, By weight percentage, it contains the following components: 5-18% silicone defoaming active agent, 15-35% polyether modified silicone dispersion, 1-5% hydrophobic fumed silica, 3-10% nonionic emulsifier, 0.5-3% thickening stabilizer, and the balance being deionized water; The organosilicon defoaming active ingredient is a composite silicone paste of hydroxyl-terminated polydimethylsiloxane and silicone resin, which is prepared by a condensation reaction between hydroxyl-terminated polydimethylsiloxane and silicone resin. The composite defoamer does not exhibit oil bleed or stratification in a medium with a pH of 11-14, and its operating temperature range is 25-85℃.
2. The composite defoamer according to claim 1, characterized in that, The silicone resin is selected from one or more of MQ silicone resin, MT silicone resin, and T silicone resin; the mass ratio of the terminal hydroxyl polydimethylsiloxane to the silicone resin is (2-10):1; the temperature of the condensation reaction is 100-180℃ and the time is 1-6 hours.
3. The composite defoamer according to claim 1, characterized in that, The polyether-modified organosilicon dispersion is prepared by hydrosilylation reaction of allyl polyoxyethylene polyoxypropylene ether and hydrogen-containing silicone oil, or by condensation reaction of hydroxyl-terminated polyether and hydrogen-containing silicone oil, or by free radical graft copolymerization of polyether and dimethyl silicone oil; the EO / PO molar ratio of its polyether side chain is (1-6):1, the number average molecular weight Mn is 800-5000, and the cloud point is 45-90℃.
4. The composite defoamer according to claim 1, characterized in that, The specific surface area of the hydrophobic fumed silica is 150-300 m². 2 / g, with a contact angle ≥130° after hydrophobic surface treatment with hexamethyldisilazane or dimethyldichlorosilane.
5. The composite defoamer according to claim 1, characterized in that, The nonionic emulsifier is selected from two or more of the following compound systems: sorbitan fatty acid ester, polyoxyethylene sorbitan fatty acid ester, alkylphenol polyoxyethylene ether, and fatty alcohol polyoxyethylene ether. The weighted average HLB value after compounding is 8-13.
6. The composite defoamer according to claim 1, characterized in that, The thickening stabilizer is selected from one or more of xanthan gum, sodium carboxymethyl cellulose, sodium polyacrylate, hydroxyethyl cellulose, and guar gum.
7. A method for preparing the composite defoamer as described in any one of claims 1-6, characterized in that, Includes the following steps: a) Mix hydroxyl-terminated polydimethylsiloxane with silicone resin in a certain proportion, stir and react at 100-180℃ for 1-6 hours, and obtain composite silicone paste after cooling. b) Dissolve the nonionic emulsifier in deionized water at 60-70℃, add the composite silicone paste, and emulsify at high speed of 3000-5000rpm for 15-30 minutes to obtain the silicone paste emulsion. c) Add the polyether-modified organosilicon dispersion to the remaining deionized water and stir to disperse evenly; d) Combine the emulsions obtained in steps b and c, add hydrophobic fumed silica, and continue high-speed shearing for 10-20 minutes; e) Add a thickening stabilizer to adjust the viscosity to 500-2000 mPa·s (25℃) to obtain the composite defoamer.
8. The application of the composite defoamer according to any one of claims 1-6 in the PCB stripping process or the PCB developing process.
9. The application according to claim 8, characterized in that, When applied to the stripping process, the stripping solution is an alkaline NaOH system or a mixed alkaline NaOH / organic amine system, with an operating temperature of 55-80℃ and an antifoaming agent addition of 0.05-0.3wt%; when applied to the developing process, the developing solution is a Na2CO3 system, with an operating temperature of 28-32℃ and an antifoaming agent addition of 0.02-0.1wt%.
Citation Information
Patent Citations
Preparation method of defoaming agent resistant to high temperature and strong alkali
CN105561634A
Preparation method of modified polyether defoaming agent for circuit board cleaning fluid
CN117398724A